IMPLIKASI SISTEM PENGENDALIAN MANAJEMEN DAN LINGKUNGAN INTERNAL TERHADAP STRATEGI BISNIS PADA KINERJA ORGANISASI - Dharmayanti, Nela; Lestari, Tri (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
Â The purpose of this research is to analyze the influence of Management Control System (SPM) which includes diagnostic control system (DCS), interactive control system (ICS), Dyinamic Tension (DT) control system, Internal Environment and Business Strategy on Organizational Performance. The data used in this research is obtained from Managerial Manufacturing Company in Banten Province. Of the 100 questionnaires distributed, the number of returned and processed questionnaires was 60 questionnaires (60%). Data is processed by using software program Partial Least Square (PLS). This research uses purposive sampling method with Middle Manager sample which is involved in the process of supervision system in Finance, Human Resource And Development, Marketing and Production. Sources of data obtained from the field research, namely by distributing questionnaires to obtain primary data and research literature (Library Research) / documentation. The results showed 1) Management Control System (SPM) which includes diagnostic control system (DCS) has an effect on Business Strategy; 2) Management Control System (SPM) which includes interactive control system (ICS) has an effect on Business Strategy; 3) Management Control System (SPM) which includes Dynamic Tension (DT) control system affecting the Business Strategy; 4) Internal Environment Affects Business Strategy; And 5) Business Strategy Affects Organization Performance.Keywords: Management Control System, Internal Environment, Business Strategy and Organization Performance